Thinning strategies of birch in Latvia, with application in a newly established field experiment - Saicane, Dagnija (SLU/Southern Swedish Forest Research Centre, 2019)
Birch (Betula pendula Roth) is an early successional species which, if grown in suitable soils with wise management, can have high and valuable production. Large-dimension birch-wood is used for saw logs and plywood production, but smaller ones for pulpwood and energy wood. During the last decades in Latvia, the area occupied by silver birch have been increasing. One of the reasons for that is that forest owners let clearcuts regenerate naturally, as a result, pioneer-species come first and another reason is abandoned agricultural land afforestation. The purpose of this long-term experiment is to find suitable thinning intensity programs for birch stands with the aim to obtain veneer quality assortment in shorter rotation time. A second aim is to study if manual pruning can be an effective additional treatment to reach the aim of high-quality timber. The experiment was implemented in south-east Latvia, in 14-years-old birch stands, which have been artificially regenerated by planting on former agriculture lands. The chosen experimental design was randomized complete block (RCB) with split plots and 5 m wide buffer zone around. Each experiment consisted of six plots and six different thinning treatments that were randomly assigned to plots. The plots were split in half and in one half of the plots branches were pruned while trees were unpruned on the other half. After first thinning quadratic mean diameter and quadratic mean height for remaining trees did not show statistically significant differences between treatments. However, basal area and volume differences between treatments were significant. Removed volumes varied considerably between various treatments; removed basal area and volume varied between 16% – 65% of initial basal area and volume dependent on treatment.